2021
DOI: 10.7150/ijbs.60384
|View full text |Cite
|
Sign up to set email alerts
|

Towards Post-Meiotic Sperm Production: Genetic Insight into Human Infertility from Mouse Models

Abstract: Declined quality and quantity of sperm is currently the major cause of patients suffering from infertility. Male germ cell development is spatiotemporally regulated throughout the whole developmental process. While it has been known that exogenous factors, such as environmental exposure, diet and lifestyle, et al, play causative roles in male infertility, recent progress has revealed abundant genetic mutations tightly associated with defective male germline development. In mammals, male germ cells undergo dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 196 publications
1
12
0
Order By: Relevance
“…When it comes to sex differentiation and germline development, the situation is more nuanced. Overall, the genetic pathways controlling these events appear largely conserved between the two species but differences were identified ( [33][34][35] for recent reviews). For example, the function of DMRT1 in male-and of the FOXL2 in female-gonadal differentiation in humans is not conserved in mice, but exists in other mammalian species [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to sex differentiation and germline development, the situation is more nuanced. Overall, the genetic pathways controlling these events appear largely conserved between the two species but differences were identified ( [33][34][35] for recent reviews). For example, the function of DMRT1 in male-and of the FOXL2 in female-gonadal differentiation in humans is not conserved in mice, but exists in other mammalian species [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For viable spermatozoa with the reproductive capability to be produced, spermatogenesis must go unhindered and undisturbed. An insult to the body or specifically directed at the reproductive organs, such as the testes, could distort spermatogenesis and impair reproductive functions in males, due to the poor quality and characteristics of sperm cells (Azhar et al, 2021; Badkoobeh et al, 2013; Omotoso et al, 2017; Tvrdá et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to point out that we must be cautious when using the findings from mouse studies to interpret the causative factors and mechanisms underlying human infertility regarding considerable differences still exist between humans and mice (Azhar et al, 2021). A recent study has shown that the metaphase checkpoint is more frequently activated than the pachytene checkpoint in human males with severe spermatogenic impairment (Enguita-Marruedo et al, 2019), which is in contrast to observations in the mouse, where knockout of the meiotic prophase genes (as we summarized above) most frequently results in pachytene checkpoint arrest.…”
Section: Mutations Of Meiotic Prophase Genes In Micementioning
confidence: 99%